IS THERE TREATMENT EFFECT OF VINPOCETINE ON AUTONOMIC DYSFUNCTION IN RATS WITH ALZHEIMER - Dolu, Nazan; SEDA GÜNDÜZ; Kara, Ali Yucel; Acer, Hale; SELDA TASAN; Khan, Azizuddin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Alzheimer'sÂ diseaseÂ (AD) shows less autonomic dysfunction. There was lack ofÂ responseÂ or prolongation of its latency in skinÂ sympatheticÂ response. Vinpocetine is a classic inhibitor of PDE1 activity. Vinpocetine treatment has been shown to enhance performance on cognitive tests in humans. The efficacy of the use of vinpocetine in clinical trials has been controversial. A comparison of multiple studies evaluating vinpocetine use in Alzheimer'sÂ diseaseÂ AD was recently conducted. Objective: Our first aim was to assess dysautonomia inÂ rat with Alzheimer'sÂ diseaseÂ AD electrophysiologically, usingÂ sympatheticÂ skinÂ responseÂ (SSR) test. The second aim in this study, evaluate of the effect of vinpocetine treatment on Alzheimer autonomic dysfunction and attention deficiency. Method: Rats were dividedÂ intoÂ four groups: Sham group (GroupÂ C, i.p. saline), Alzheimer group (GroupÂ A),Â Vinpocetine group (Group V, 5mg/kg, every other day, i.p.), Alzheimer+ Vinpocetine group (Group AV). Alzheimer'sÂ diseaseÂ was induced in old maleÂ ratsÂ by AlCl3 (40 mg/kg i.p.) and D-Galactose (90 mg/kg) daily for 6 weeks. Then Skin Conductance Level (SCL), which is a sympathetic skin response parameter, was measured as tonic (no-stimuli period, 2 min) and phasic SSR (simultaneouslyÂ with 15 auditory stimuli, 10 min). TonicÂ SSR is useful to investigate general states of arousal and alertness, while phasic SSR is useful to study multifaceted attentional processes (related to novelty, intensity). Results: SCL was difference among groups (tonic: F=21.47, pâ‰¤0.000; phasic: F=9.86, pâ‰¤0.000). Skin conductance level (SCL) was statistically lower in Group A than Group C (pâ‰¤0.005) and Group V (pâ‰¤0.000). SCL of Group V was statistically higher then Group C (pâ‰¤0.04), Group A (pâ‰¤0.000) and Group AV (pâ‰¤0.000). SCL of Group AV was lower than Group C's (pâ‰¤0.01). Conclusion: There were no statistically difference between Group A and Group AV. We concluded that autonomic disturbances accompaniedÂ Alzheimer'sÂ diseaseÂ and vinpocetine treatment couldn't ameliorate this disturbance. Â Keywords: Autonomic dysfunction, Dysautonomia, Inhibitor, Skin conductance level, SympatheticÂ skinÂ response Â